Progesterone Antagonizes Dexamethasone-Regulated Surfactant Proteins In Vitro. (August 2019) - Kunzmann, Steffen; Ottensmeier, Barbara; Speer, Christian P.; Fehrholz, Markus
Pregnant women at risk of preterm labor routinely receive glucocorticoids (GCs) and frequently also progesterone. Administration of GCs accelerates intrauterine surfactant synthesis and lung maturation, thereby reducing the incidence of neonatal respiratory distress syndrome; progesterone has the potential to prevent preterm birth. Little is known about possible interactions of GCs and progesterone. Our aim was to clarify whether progesterone can affect dexamethasone (DXM)-regulated expression of surfactant protein A (SP-A), SP-B, and SP-D in lung epithelial cells. H441 cells were exposed to DXM and progesterone and expression of SPs was analyzed by quantitative real-time polymerase chain reaction and immunoblotting. Although progesterone had no direct effect on the expression of SP-B, DXM-mediated induction was inhibited dose dependently on the transcriptional (64 µM [ P < .0001], 32 µM [ P = .0005], 16 µM [ P = .0019]) and the translational level. Furthermore, progesterone inhibited stimulatory effects of other GCs as well. While exogenous tissue growth factor β1 (TGF-β1) inhibited DXM-induced SP-B expression (messenger RNA [mRNA]: P = .0014), progesterone itself did not influence TGF-β1 mRNA expression and/or TGF-β1/Smad signaling, demonstrating that TGF-β1 and/or Smad activation is not involved. The inhibitory effect of progesterone could be imitated by the GC and progesterone receptor (PR) antagonist RU-486, but not by the specific PR antagonist PF-02413873, indicating that progesterone acts as a competitive antagonist of DXM. The effect of progesterone on DXM-regulated genes was not specific for SP-B, as expression of SP-A and SP-D mRNAs was also antagonized. The present study highlights a new action of progesterone as a potential physiological inhibitor of GC-dependent SP expression in lung epithelial cells. The clinical relevance of this in vitro finding is currently unknown.